Type 2 macrophages and Th2 CD4+ cells in interstitial lung diseases (ILDs): an overview - Partida-Zavala, Neftali; Ponce-Gallegos, Marco Antonio; Buendía-Roldán, Ivette; Falfán-Valencia, Ramcés (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Interstitial lung diseases (ILDs) are a heterogeneous group characterized mainly by damage to pulmonary parenchyma, through histopathological processes such as granulomatous pneumopathy, inflammation and fibrosis. Factors that generate susceptibility to ILDs include age, exposure to occupational and environmental compounds, genetic, family history, radiation and chemotherapy/immunomodulatory and cigarette smoke. IFN-γ, IL-1β, and LPS are necessary to induce a classical activation of macrophages, whereas cytokines as IL-4 and IL-13 can induce an alternative activation in macrophages, through the JAK-STAT mediated signal transduction. M2 macrophages are identified based on the gene transcription or protein expression of a set of M2 markers. These markers include transmembrane glycoproteins, scavenger receptors, enzymes, growth factors, hormones, cytokines, and cytokine receptors with diverse and often yet unexplored functions. Fibrotic lung disorders may have a M2 polarization background. The Th2 pathway with an elevated CCL-18 (marker of M2) concentration in the bronchoalveolar lavage fluid (BALF) is linked to fibrosis in ILDs. Besides the role of M2 in tissue repair and ECM remodeling, activated fibroblasts summon and stimulate macrophages by producing MCP-1, M-CSF and other chemokines, as well as activated macrophages secrete cytokines that attract and stimulate proliferation, survival and migration of fibroblast mediated by platelet-derived growth factor (PDGF)